Crisis and organised control: The COVID-19 Pandemic and Power of Surveillance - Marković Savić, Olivera S. (Sociološki pregled, 2020)
In this text, we consider the short term and long-term consequences of the COVID-19 epidemic among people throughout the world. In many societies, as a result of the health danger, governments have intervened by denying basic social and political rights. Because of these changes, economy has experienced a crisis whose effects many compare to the Great Depression of the last century. By dealing with the new problems, many countries have enforced measures of quarantine and closed their borders. The answer to the problems has not shown international solidarity, but state-centrism. The text first discusses what the old anti-epidemic measures brought to modern societies that had to be resorted to in preventing the spread of the epidemic. This is followed by an attempt to predict the possible long-term consequences for the functioning of social structures and government systems. As countries increase control and penetration into the sphere of everyday life of their citizens, in which they are substantially aided by new technologies, this trend can be expected to continue. On the other hand, citizens will lend support with the enforcement of such control in exchange for the sense of security. In the long run, such processes indicate the possibility that countries will emerge stronger from this crisis, although until recently it was thought that they had weakened under the impact of globalization.